10.1001/TESTjama.2012.4607 (CrossRef Listing of Deleted DOIs, 2000)
IMPORTANCE: Prior research has demonstrated higher rates of disenrollment from Medicare Advantage (MA) among people with greater health care needs. Yet, less is known about how disenrollment responds to changes in medical complexity, whether disenrollment varies by the degree of complexity, and how these patterns differ by state Medigap protections and MA plan characteristics. OBJECTIVE: To examine changes in MA plan disenrollment following the development of new complex medical conditions and assess heterogeneity by number of conditions, state Medigap policy, and plan characteristics. DESIGN, SETTING, AND PARTICIPANTS: This cohort study used Medicare enrollment and claims data from 2016 to 2021. The study population included beneficiaries continuously enrolled in MA in 2016 without complex medical conditions from 2016 through 2018. A treatment group developed a new complex condition in 2019; a comparison group did not develop a complex condition through 2021. Data were analyzed from December 1, 2025, to March 1, 2026. EXPOSURE: Development of 1 or more new complex medical conditions in 2019, including acute myocardial infarction, Alzheimer disease and related dementia, atrial fibrillation, chronic kidney disease, chronic obstructive pulmonary disease, depression, congestive heart failure, or stroke. MAIN OUTCOMES AND MEASURES: Annual disenrollment from the prior year MA plan, which included disenrollment to traditional Medicare (TM) or switching to another plan within MA. Difference-in-differences models with beneficiary and year fixed effects were estimated and converted to differences in percentage points. RESULTS: The analytic sample included 1 054 926 beneficiaries, including 219 942 (mean [SD] age, 75.3 [6.3] years; 54.6% female) who developed new complex conditions in 2019 and 834 984 (mean [SD] age, 73.8 [5.6] years; 56.7% female) who did not develop a new complex condition in 2019. Developing any new complex condition was associated with an increase of 3.3 (95% CI, 3.1-3.5) percentage points (pp) in MA disenrollment, including an increase of 2.8 (95% CI, 2.7-2.9) pp in disenrollment to TM. The number of new complex conditions was associated with increased disenrollment, from 1.4 (95% CI, 1.3-1.6) pp for 1 condition to 12.8 (95% CI, 11.6-13.9) pp for 4 or more conditions. Disenrollment to TM was 1.5 (95% CI, 0.9-2.1) pp higher among beneficiaries residing in states with Medigap guaranteed issue and community rating protections. CONCLUSIONS AND RELEVANCE: In this study, development of new complex medical conditions was associated with higher MA disenrollment, particularly to TM and in states with Medigap protections, and the magnitude increased with medical complexity. These findings highlight how changes in health status and state policy may shape Medicare coverage decisions.